Selected allergic diseases of the gastrointestinal tract - Andrzej Kuźmiński; Michał Przybyszewski; Małgorzata Graczyk; Magdalena Żbikowska-Götz; Natalia Sokołowska-Ukleja; Alina Tomaszewska; Zbigniew Bartuzi (Gastroenterology Review)
Clinical symptoms of food allergy may affect not only the digestive tract, but also the respiratory system, skin, or cardiovascular system. They may manifest themselves as gastrointestinal problems, asthma attacks, hives, or anaphylactic shock. Allergic reactions of the gastrointestinal tract may be IgE-independent (oral anaphylaxis syndrome, acute gastrointestinal reactions), mixed (eosinophilic gastrointestinal disorders), or IgE-independent (food-induced enterocolitis, proctitis, or enteropathy). The most serious conditions in which allergic background plays or can play an important role are: oral anaphylaxis syndrome, aphthous stomatitis, reflux disease, acute and chronic allergic reactions of gastric mucosa, irritable bowel syndrome, and eosinophilic gastrointestinal disorders.